Tanaman Sambung Nyawa (Gynura procumbens) sebagai Antihiperglikemi - Ayu Agustira; Iswandi Darwis; Dian Isti angraini (CV. Jasa Sukses Abadi, 2019)
Diabetes mellitus is a disease with impaired carbohydrate metabolism identified by high blood glucose levels (hyperglycemia) and the presence of glucose in urine (glycosuria) that occurs due to abnormal insulin secretion, insulin activity or both. Diabetes mellitus is one of the biggest cause of deaths in Indonesia, which is proven by the Data of Sample Registration Survey in 2014 where diabetes became the third cause of death in Indonesia after stroke and coronary heart disease. If not handled properly, it will affect the decrease in productivity, increase disability, premature death, etc. Sambung Nyawa Plants (Grynura Procumbens) has been widely used as a traditional medicine as antihyperglycemic. Sambung Nyawa Plants contains saponin compounds, flavonoids, and alkaloids, which can reduce blood glucose levels. The mechanism of reducing glucose by Sambung Nyawa Plants is by secreting insulin in β-pancreatic cells and regenerating β-pancreatic cell damage, as an antioxidant that can bind free radicals, there by reducing insulin resistance, and inhibiting alpha amylase and alpha glucosidase which can break carbohydrates into monosaccharides that can be absorbed by the intestine